Public Service Broadcasting in the Age of Information Capitalism - Ruth Elizabeth Tomaselli (Communicare)
This paper looks at two temporary phenomena: Information capitalism, and public service broadcasting. The crux of the paper is the question whether the ideal of public service broadcasting can survive the new technological and economic arrangements Impinging on broadcasting; and secondly, whether the public service ethos is worth saving, In view of all the shortcomings and Inherent contradictions within the system. To answer these questions, we need to clarify what we mean by technological revolution, or, what I feel is more appropriately referred to as "information capitalism". The paper will focus on what I see to be some of the key cultural, ideological and political questions thrown up by this new order, and how these changes may affect the present and future systems of broadcasting regulations and programme content. The paper also looks at what is meant by public service broadcasting, and how the concept has been applied in the South African context. It outlines some of the main crises to have bedevilled the system internationally, and focuses particularly on the somewhat spurious claim that public service broadcasting is politically neutral and non-aligned. After reviewing the criticisms levelled at the alternative to Public Service Broadcasting: Deregulated broadcasting, the paper concludes that the former is indeed worth saving, but only as part of the broader broad casting and televisual arrangements within a "mixed economy" which would include deregulated television arrangements